Life Expectancy After Cervical En Bloc Laminoplasty: Analysis of Data Following More Than 20 Years. Issue 7 (1st April 2017) - Kawaguchi, Yoshiharu; Nakano, Masato; Yasuda, Taketoshi; Seki, Shoji; Hori, Takeshi; Suzuki, Kayo; Makino, Hiroto; Kanamori, Masahiko; Kimura, Tomoatsu
Abstract : Study Design: Case series. Objective: To clarify the following questions How long after cervical laminoplasty did the patients die? What were the causes of the death? Was the severity of the neurological dysfunction related to early death? Summary of Background Data: Life expectancy in patients with cervical myelopathy is unclear. Cervical laminoplasty was performed in 216 patients between 1981 and 1994. It was possible to follow 148 patients for more than 20 years. We used the data of the 68 survivors and the 80 patients had already died. Methods: As for the patients who died by the final follow-up, the survival rate was analyzed by a Kaplan-Meier plot; the results were compared between the patients with cervical spondylosis (CS) and the patients with ossification of the posterior longitudinal ligament (OPLL). The causes of the death were assessed. The neurological evaluation was graded using the score devised by the Japanese Orthopaedic Association (JOA). The pre- and postoperative scores were compared between the patients in the died group (D group) and the surviving patients group (S group). Results: The mean period from surgery to death was 13.4 ± 7.4 years. There was no difference in the survival rate between patients with CS and patients with OPLL. The most frequent cause of death was malignant tumor followed by ischemic heart disease. Preoperative JOA score in the D group was lower than that in the S group. There was no statistical difference in postoperative JOA score between the two groups. Conclusion: The patients who underwent cervical laminoplasty caused by compression myelopathy due to CS and OPLL had a long life expectancy, averaging more than 13 years. Life expectancy did not differ between patients with CS and patients with OPLL. Neurological deficit did not directly affect the life expectancy. Level of Evidence: 4